Association of Pre-stroke Frailty With Prognosis of Elderly Patients With Acute Cerebral Infarction: A Cohort Study - Yang, Fuxia; Li, Nan; Yang, Lu; Chang, Jie; Yan, Aijuan; Wei, Wenshi (Frontiers in Neurology, 2022)
Background Frailty is a state of cumulative degradation of physiological functions that leads to adverse outcomes such as disability or mortality. Currently, there is still little understanding of the prognosis of pre-stroke frailty status with acute cerebral infarction in the elderly. Objective We investigated the association between pre-stroke frailty status, 28-day and 1-year survival outcomes, and functional recovery after acute cerebral infarction. Methods Clinical data were collected from 314 patients with acute cerebral infarction aged 65–99 years. A total of 261 patients completed follow-up in the survival cohort analysis and 215 patients in the functional recovery cohort analysis. Pre-stroke frailty status was assessed using the FRAIL score, the prognosis was assessed using the modified Rankin Scale (mRS), and disease severity using the National Institutes of Health Stroke Scale (NIHSS). Results Frailty was independently associated with 28-day mortality in the survival analysis cohort [hazard ratio (HR) = 4.30, 95% CI 1.35–13.67, p = 0.014]. However, frailty had no independent effect on 1-year mortality (HR = 1.47, 95% CI 0.78–2.79, p = 0.237), but it was independently associated with advanced age, the severity of cerebral infarction, and combined infection during hospitalization. Logistic regression analysis after adjusting for potential confounders in the functional recovery cohort revealed frailty, and the NIHSS score was significantly associated with post-stroke severe disability (mRS > 2) at 28 days [pre-frailty adjusted odds ratio (aOR): 8.86, 95% CI 3.07–25.58, p < 0.001; frailty aOR: 7.68, 95% CI 2.03–29.12, p = 0.002] or 1 year (pre-frailty aOR: 8.86, 95% CI 3.07–25.58, p < 0.001; frailty aOR: 7.68, 95% CI 2.03–29.12, p = 0.003). Conclusions Pre-stroke frailty is an independent risk factor for 28-day mortality and 28-day or 1-year severe disability. Age, the NIHSS score, and co-infection are likewise independent risk factors for 1-year mortality.